كتاب تعليم المتعلم تأثيره ودوره وسط تربية الشخصية لدى طلاب المعاهد الإسلامية - Moh. Ulin Nuha (Pascasarjana Universitas Wahid hasyim Semarang, 2020)
AbstractThis study aims to find answers to how the position of the book ta'limul muta'allim in Islamic boarding schools and the extent of its influence in the formation of a strong personality. This field research uses phenomenological theory and comes to several conclusions, namelythe book of Ta'limul Muta'allim has an important role in the formation of a strong personality in Islamic boarding schools. The role of this book is not just a mere formality, but is very applicable in everyday life. Another conclusion from this research is that the book of Ta'limul Muta'allim has a special position compared to other books.